Lightning search algorithm for economic dispatch solution considering practical constraints and transmission loss - A. Rahimoon, Asif; Noor Abdullah, Mohd; Mohd Yassim, Halyani; Raza, Asif; A.Soomro, Shafique (2024)
This paper presents the investigation of the Lightning Search Algorithm (LSA) performances for solving the Economic Dispatch (ED) problem. The main purpose of ED problem is to determine the optimal power output of the committed generators to satisfy the load demand and operational constraints. The LSA employs principles inspired by the natural phenomenon of lightning and the mechanism of step leader propagation. The ED constraints such as valve point effect (VPE), power balance (PB), ramp rate limits (RRL), prohibited operating zone (PoZ) with and without power losses are considered to solve the ED problem. The proposed LSA has been tested on three different test systems comprised of 6, 13 and 38-generating units to demonstrate the effectiveness of the proposed LSA. The result reveals that the proposed LSA performs well for cost minimization ($/h) compared to existing algorithms